Preliminary Analysis of A Low-Cost Greenhouse For Salt Production in Tuban, East Java, Indonesia - A. A. Jaziri; A. A. Amin; M. I. Syafi’i; W. Setiawan; A. A. Prihanto (Future Science)
Salt is an important material for industrial point of view. It is not only used in food industry, but also applied in wide range of industries. For instance, chemical, oil drilling, and animal feed industries, even less than half of salt needs used to household consumption. It is crucial to ensure salt production in Indonesia reaches the national target (3.7 million tons in 2017) due to relatively low technology and production level. Traditionally, salt is produced by adding raw material of brackish water from river with the value of 0-3 oBe. Then, the raw material is precipitated and evaporated for 40-45 days to produce salt with the value of 26 oBe. The productivity of the traditionally salt production is 30-50 tons/ha with the low quality of salt around 80% of NaCl. Recently, salt production technology is developed to facilitate farmers consisted of geomembrane and filtering-threaded technology. By those technologies, the productivity and quality of salt could be increased around 80 tons/ha and NaCl (90%), respectively. However, both technologies in producing salt was proved less effective due to unpredictable weather conditions. Therefore, greenhouse technology is proposed to be used for salt production for several good reasons. This paper describes the preliminary analysis of a low-cost greenhouse designed as a house model that uses bamboo, mono-layer and low density polyethylene plastics. The results confirmed that the yield of salt produced by greenhouse significantly incresed compared with prior technologies and the NaCl content increased as well. The cost of greenhouse was IDR 2,100,000 and easy to assembly. This proposed technology would be a promising and prospecting approach to support sustaibable salt production in Indonesia.